Methods of predicting relapsing hemorrhage. - Trofimov, M. V.; Kryshen, V. P.; Gaponov, I. V. (Medicni Perspektivi, 2018)
In this article the authors presented their own original methods for predicting ulcerous gastroduodenal bleeding defended by Patent of Ukraine. The implementation of these procedures led to substantial lowing of recurrent hamorrhage rate – more than twice. All methods have pathogenetic foundation and are based on ulcerogenesis mechanisms revealed during the longlasting complex clinical and experimental research. In such a way surgeons obtain some possibilities of early diagnostics of bleeding relapses and adequate treatment and effective hemorrhage prevention accordingly.